Hypoalbuminemia and Elevated CRP are Risk Factors for Deep Infections and Urinary Tract Infections After Lumbar Spine Surgery in a Large Retrospective Patient Population. Issue 1 (January 2023) - Yoshida, Brandon; Nguyen, Ailene; Formanek, Blake; Alam, Milad; Wang, Jeffrey C.; Buser, Zorica
Study Design: Retrospective cross-sectional study. Objectives: To determine if pre-operative albumin and CRP can predict post-operative infections after lumbar surgery. Methods: Patients who underwent an anterior lumbar interbody fusion (ALIF), posterior lumbar interbody fusion (PLIF), or lumbar discectomy were identified using a patient record database (PearlDiver) and were included in this retrospective study. Patients were stratified by Charlson Comorbidity Index (CCI) scores and pre-operative albumin and CRP status. Post-operative complications included deep infections and urinary tract infections within 3 months of the surgery and revisions within 1 year of the surgery. Results: 74, 280 patients were included in this study. 21, 903 had pre-operative albumin or CRP lab values. 7, 191 (33%), 12, 183 (56%), and 2, 529 (12%) patients underwent an ALIF, PLIF, and a lumbar discectomy, respectively. 16, 191 did not have any complication (74%). The most common complication was UTI (16%). Among all patients, hypoalbuminemia was a significant risk factor for deep infection and UTI after ALIF, deep infection, UTI, and surgical revision after PLIF, and deep infection after lumbar discectomy. Elevated CRP was a significant risk factor for deep infection after ALIF, UTI after PLIF, and deep infection after lumbar discectomy in patients with a CCI ≤ 3. Conclusions: Pre-operative hypoalbuminemia and elevated CRP were significant risk factors for deep infection, UTI, and/or revision, after ALIF, PLIT, and/or lumbar discectomy. Future studies with a larger population of patients with low albumin and high CRP values are needed to further elaborate on the current findings.